The psychology of gratitude - Emmons, Robert A.; McCullough, Michael E. (Series in affective science., 2004)
Gratitude, like other positive emotions, has inspired many theological and philosophical writings, but it very little vigorous, empirical research. In an effort to remedy this oversight, this volume brings together contributors from various disciplines to examine what is known of this emotion.